2018
DOI: 10.17738/ajes.2017.0012
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar arsenic, copper, nickel, uranium, and yttrium-rich stone coatings in a high mountain stream in the Austrian Alps

Abstract: Peculiar coatings rich in arsenic, copper, nickel, uranium, and yttrium were found to cover stones in a high mountain stream downstream of the confluence of small acidic tributaries, which emerge at the front of the Krummgampen rock glacier (Ötztal Alps, Tyrol, Austria). The hard mineral coatings are characterized by a white color, a x-ray amorphous structure and showed properties of hydrous aluminium silicates like allophane (Al O (SiO ) x n H O) and/or imogolite (Al SiO (OH) ). Main constituents of the coati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 12 publications
2
11
1
Order By: Relevance
“…However, the knowledge on the impact of climate change on permafrost thawing processes, and, consequently, on the chemical and biological quality of headwaters emerging from Alpine rock glaciers is still scarce (Colombo et al, 2018). Despite the limit posed by the small number of headwater surveyed, the present study confirms the results obtained by previous investigations on chemical features and biodiversity of permafrost-fed headwaters waters in the Central Alps (Thies et al, 2007(Thies et al, , 2013(Thies et al, , 2018Ilyashuk et al, 2014;Lösch et al, 2015;Thaler et al, 2015), and provides new insight on aspects scarcely considered so far.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the knowledge on the impact of climate change on permafrost thawing processes, and, consequently, on the chemical and biological quality of headwaters emerging from Alpine rock glaciers is still scarce (Colombo et al, 2018). Despite the limit posed by the small number of headwater surveyed, the present study confirms the results obtained by previous investigations on chemical features and biodiversity of permafrost-fed headwaters waters in the Central Alps (Thies et al, 2007(Thies et al, , 2013(Thies et al, , 2018Ilyashuk et al, 2014;Lösch et al, 2015;Thaler et al, 2015), and provides new insight on aspects scarcely considered so far.…”
Section: Discussionsupporting
confidence: 90%
“…Despite the expected change in the relative importance of the major components of the Alpine cryosphere, the understanding of the possible cascading effects of permafrost degradation on water quality and ecology of Alpine freshwater is still largely incomplete. Insights into the effects of rock glacier thawing on inorganic chemistry of Alpine headwaters were provided by some recent case studies (Krainer et al, 2007;Thies et al, 2007Thies et al, , 2013Thies et al, , 2018Colombo et al, 2018a;Engel et al, 2018). Compared to waters fed by glacier melt or atmospheric precipitation and groundwater, headwaters emerging from active rock glaciers are commonly characterised by higher electrical conductivity (EC) and concentration of major ions, in particular Mg 2+ , Ca 2+ and SO 4 2- (Colombo et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the origin of the SO 4 discharged by rock glaciers, most studies hypothesized oxidation of sulfide (Ilyashuk et al 2018;Williams et al 2006;Thies et al 2017) or dissolution of gypsum generated by sulfide oxidation (Lecompte et al 2008), because of the ubiquitous presence of pyrite in metamorphic rocks. Discharge of SO 4 as a consequence of gypsum or anhydrate dissolution has been reported less frequently (Colombo et al 2019;Rogora et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This extension could explain the observed discharge rates and temperatures at the Tuxbachquelle. Hydrological studies in other Alpine regions showed that rock glaciers can impact the water quality extensively and can yield a base runoff of 70 to 100 L/s during summer months (Nickus et al 2015;Thies et al 2013Thies et al , 2017Engel et al 2019).…”
Section: Catchment Areamentioning
confidence: 99%